JST PENERAPAN JARINGAN SYARAF TIRUAN DENGAN METODE PERCEPTRON UNTUK MENENTUKAN JENIS E-LEARNING (STUDI KASUS DI STMIK HANG TUAH PEKANBARU) - Yulisman Yulisman (Jurnal Ilmu Komputer, 2017)
Abstract The application of E-Learning types that correspond to the characteristics of the E-Learning system can be determined by the user by filling out a questionnaire about the characteristics of the E-Learning System. Many types of E-Learning that have been used by the institution. To determine the type of E-Learning that is appropriate to the characteristics of the E-Learning system can be done by the user by filling out the assessment questionnaire about the characteristics of the E-Learning System. The data processing results of the questionnaire to the application of the Neural Network with the Perceptron method. Neural network is an information processing system that has characteristics similar to a network of nerve biology. Perceptron is a simple network that is usually used to classify a particular type of pattern that is often known as a linear separation. From the calculations that researchers do manually or testing of the training data and test data in accordance with the training measures Perceptron defined in equation f (net) = t (yi), and error = 0 to determine kesusksesannya, then from training data and test data produces the correct target and in accordance with the expected results, which means that the method Perceptron applied were able to predict the type of E-Learning in accordance with the characteristics of E-Learning system is correct and produce the same target with the data results of the questionnaire from the user. Calculation of percentage of E-Learning used STMIK Hang Tuah Pekanbaru corresponding characteristics of the system of E-Learning and Evaluation Model ISO 9126 elearning.htp.ac.id results obtained with the value -1 = No, the performance of 20%, and a value of 1 = Yes, performance 80% and the error = 0 of 20 training data and test patterns. kuliah.htp.ac.id with a value of -1 = No, the performance of 45%, and a value of 1 = Yes, the performance of 55% and error = 0 of 20 training data and test patterns. edmodo.com/es3jelita with a value of -1 = No, the performance of 80%, and a value of 1 = Yes, the performance of 20% and error = 0 of 20 training data and test patterns. Abstrak E-Learning adalah merupakan salah satu media pembelajaran yang memanfaatkan teknologi informasi yang didukung oleh perangkat elektronik serta jaringan internet. Banyak jenis E-Learning yang telah digunakan oleh lembaga pendidikan. Untuk menentukan jenis E-Learning yang sesuai dengan karakteristik sistem E-Learning bisa dilakukan penilaian oleh user dengan mengisi kuesioner tentang karakteristik sistem E-Learning. Pengolahan data hasil dari kuesioner tersebut bisa dengan penerapan Jaringan syaraf tiruan dengan metode Perceptron. Jaringan Syaraf Tiruan adalah sistem pemrosesan informasi yang memiliki karakteristik mirip dengan jaringan syaraf biologi. Perceptron merupakan jaringan sederhana yang biasanya digunakan untuk mengklasifikasikan suatu pola tipe tertentu yang sering dikenal dengan pemisahan secara linear. Dari perhitungan yang peneliti lakukan secara manual atau pengujian terhadap data latih dan data uji yang sesuai dengan langkah-langkah pelatihan Perceptron yang sudah ditetapkan dalam persamaan f(net)= t(yi), dan error = 0 untuk menentukan kesusksesannya, maka dari data latih dan data uji menghasilkan target yang benar dan sesuai dengan hasil yang diharapkan, yang berarti bahwa metode Perceptron yang diterapkan mampu untuk memprediksi jenis E-Learning yang sesuai dengan karakteristik sistem E-Learning sudah benar dan menghasilkan target yang sama dengan data hasil kuesioner dari user. Perhitungan Persentase E-Learning yang digunakan STMIK Hang Tuah Pekanbaru yang sesuai karakteristik sistem E-Learning Model ISO 9126 dan Evaluasi didapat hasil elearning.htp.ac.id dengan nilai -1=Tidak, performance 20%, dan nilai 1=Ya, performance 80% dan error =0 dari 20 pola data latih dan uji. kuliah.htp.ac.id dengan nilai -1=Tidak, performance 45%, dan nilai 1=Ya, performance 55% dan error =0 dari 20 pola data latih dan uji. edmodo.com/es3jelita dengan nilai -1=Tidak, performance 80%, dan nilai 1=Ya, performance 20% dan error =0 dari 20 pola data latih dan uji.